PENGARUH AROMATERAPI LEMON OIL TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI POSYANDU LANSIA DESA SUWARU KECAMATAN PAGELARAN - wyssie ika sari (Health Care Media, 2022)
Hypertension is the increase of blood pressure of diastolic and of sistolic which an intermitent. Hypertension becomes a big problem to elderly wich the increasing of age . Hypertension if don’t handle unattended hypertension will heart attack, stroke, renal failure even disesase.. One of effort to overcome hypertension is by conducting lemon oil aromatherapy. Lemon oil contents of flavonoid and limonene which are to overcome high blood pressure. This research aimed to know influence of lemon oil aromatherapy effect towards blood pressure change on the elderly with hypertension in Posyandu Lansia Suwaru Village Kecamatan Pagelaran. This type of research is quasi experiment with pre and post test with controle group. A sampling technique used by purposive sampling, consisty of 84 respondents. Analysis of the data used to determine the differences between the mean blood pressure in each group is statistical test of wilcoxon and mann-whitney u. The result of wilcoxon test showed there was differences between pre and post lemon oil aromatherapy treatment which the significancy = 0,000 ( p < 0,05) and result of mann-whitney u test showed that lemon oil aromatherapy effect on changes in blood pressure with value of significancy = 0,006 ( p < 0,05). The Conclusion of this research is that influence of lemon oil aromatherapy effect towards blood pressure change on the elderly with hypertension.